Penerapan Metode Multi-Attributive Border Approximation Area Comparison Pada Sistem Pendukung Keputusan Penentuan Penerima Bantuan Pangan Non Tunai - Sanjaya, Donny; Nababan, Arif Hamied; Sinuhaji, Nirwan; Siregar, Dini Rizqi Dwikunti; Danur, Surizar Rahmi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Non-Cash Food Assistance (BPNT) is a type of assistance managed by the Ministry of Social Affairs. The problem that often occurs when selecting recipients of non-cash food assistance previously was choosing families receiving non-cash food assistance without complying with the specified requirements or criteria. In the selection of families receiving non-cash food assistance, there is still a family attitude such as the village head and his staff who choose families receiving non-cash food assistance. This is certainly very bad, resulting in poor people not getting assistance and will also cause social jealousy among residents and not produce community welfare. A decision support system (DSS) is a system that is able to provide problem-solving capabilities and communication capabilities for problems with semi-structured and unstructured conditions. In the decision support system, the MABAC method can be applied which is able to produce the best decisions and several inputted alternatives. The results obtained from the process carried out were that A4 was the selected alternative with the highest value, namely 0.602